Reliability of a new scoring system for intraarticular mineralization of the knee: Boston University Calcium Knee Score (BUCKS). Issue 6 (June 2020) - Guermazi, A.; Jarraya, M.; Lynch, J.A.; Felson, D.T.; Clancy, M.; Nevitt, M.; Lewis, C.E.; Torner, J.; Neogi, T.
Summary: Background: The role of intra-articular mineralization in osteoarthritis (OA) is unclear. Its understanding may potentially advance our knowledge of knee OA pathogenesis. We describe and assess the reliability of a novel computed tomography (CT) scoring system, the Boston University Calcium Knee Score (BUCKS) for evaluating intra-articular mineralization. Methods: We included subjects from the most recent study visit of the Multicenter Osteoarthritis Study (MOST) Study, a NIH-funded longitudinal cohort of community-dwelling older adults with or at risk of knee OA. All subjects underwent CT of bilateral knees. Each knee was scored at 28 scored locations (14 for cartilage, 6 for menisci, 6 for ligaments, 1 for joint capsule, and 1 popliteal-tibial vessels). A single musculoskeletal radiologist scored cartilage and meniscus subregions, as well as vascular calcifications assigning to each a score ranging from 0 to 3. The joint capsule, medial and lateral posterior meniscal roots, anterior cruciate ligament (ACL)/posterior cruciate ligament (PCL) and 2 collateral ligaments [medial collateral ligament (MCL)/lateral collateral ligament (LCL)] were each scored 0 or 1 for absence or presence of mineralization. To assess reliability, 31 subject CTs were reread 12 weeks later by the same reader and by a second reader and agreement was evaluated using a weighted kappa. Results: The intra-reader reliability ranged from 0.92 for ligaments to 1.0 for joint capsule. The inter-reader reliability ranged from 0.94 for cartilage and ligaments, to 1.0 for joint capsule. Conclusion: BUCKS demonstrated excellent reliability and is a potentially useful CT-based tool for studying the role of calcium crystals in knee OA.